Strength and self-desiccation of slag-cemented paste backfill at early ages: Link to initial sulphate concentration. (May 2018) - Li, Wenchen; Fall, Mamadou
Abstract: This paper presents the results of an experimental study on the early age strength and changes in the self-desiccation process of cemented paste backfill (CPB) that contains blast furnace Slag (Slag-CPB) and sulphate. Slag-CPB samples with different initial sulphate concentrations (0, 5000, 15, 000 and 25, 000 ppm) are prepared and cured in well-sealed molds at early ages (1, 3, 7 and 28 days) in room temperature (∼23 °C). Mechanical and hydraulic conductivity tests are performed on the samples, in which the suction and electrical conductivity of the Slag-CPB specimens are monitored. Furthermore, microstructural analyses are conducted on the Slag-CPB and slag-cement paste samples. The results show that sulphate can have a positive or negative effect on the early age strength and self-desiccation of Slag-CPB, i.e., cause an increase or decrease in strength and acceleration or reduction in the amount and rate of self-desiccation, depending on the initial sulphate content and curing time. This study also shows that an understanding of the positive or negative effect of sulphate on the early strength and self-desiccation of Slag-CPB is critical for designing cost-effective CPB structures with high early strength, speeding up mining cycles or assessing the deterioration of CPB caused by high sulphate attack to ensure safety in mining.